« Je suis ce qui me manque » : quelques réflexions sur le statut ontologique des Yeux baissés de Tahar Ben Jelloun - Zdrada-Cok, Magdalena (Romanica Silesiana)
This article is devoted to the novel Les yeux baissés (1991) by Tahar Ben Jelloun and it analyses the literary games that are to question the ontological status of this piece of art. The analysis focuses on the hypertextual strategies (parody, pastiche), intertextual strategies (literary allusion and self-quotation), and narrative strategies (mise en abyme, metalepse), which lead to destabilization of the two genre components of Les yeux baissés, an epic story and a novel. Having appealed to the two literary traditions, the North African and the European one, Tahar Ben Jelloun strives to transgress, or, to go even further, to defy those two traditions. At the same time, he creates the dialogic and open form of the novel. Les yeux baissés, as a spectrum of irony and self-defiance, becomes the place of inter-cultural and intro-cultural dialogue, practicing polyphony, so typical of each culture that it goes beyond its limits. Key words: Eastern epic story, French novel, defiance of realistic aesthetics, parody, inter-cultural dialogue.